The autonomy of the Åland islands : constitutional and international law challenges - Gudmundur Alfredsson; Lindholm, Göran (Brill/Nijhoff, 2024)
"Published on occasion of the 100 year anniversary of the Åland Islands' autonomy, this book brings up and discusses a number of challenging issues, from constitutional and international law perspectives, concerning both the Åland situation and autonomy in general. Among the questions raised are: Is autonomy part of international law and which international organisations may have jurisdiction? Is autonomy a human right or is it about the prevention of violent conflicts? Does the Åland Autonomy constitute a useful model for other minority groups? Do the Åland Islands stand to benefit from anything in international law, be it substantive or procedural?"-- Provided by publisher.
Keywords: Åland (Finland) -- International status.; Self-determination, National -- Finland -- Åland.; Constitutional law -- Finland -- Åland.; Neutrality -- Finland -- Åland.; Demilitarization (International law); Åland (Finland) -- Politics and government.; Åland (Finlande) -- Statut international.; Droit des peuples à disposer d'eux-mêmes -- Finlande -- Åland.; Neutralité -- Finlande -- Åland.